2022
DOI: 10.1111/nph.18162
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of flower transpiration during abiotic stress in annual plants

Abstract: Summary Heat waves occurring during droughts can have a devastating impact on yield, especially if they happen during the flowering and seed set stages of the crop cycle. Global warming and climate change are driving an alarming increase in the frequency and intensity of combined drought and heat stress episodes, critically threatening global food security. Because high temperature is detrimental to reproductive processes, essential for plant yield, we measured the inner temperature, transpiration, sepal sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(157 citation statements)
references
References 84 publications
3
149
0
Order By: Relevance
“…The thermoregulating effect of transpiration most directly affects internal and surface temperatures of crop tissue 44 . As a result, leaves, flowers and even the wider vegetated canopy can be cooler or warmer than the surrounding air 68,72 . In China and India, these crop influences on surface climate extend through the troposphere 73 and influence large-scale circulation and rainfall patterns 74 .…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The thermoregulating effect of transpiration most directly affects internal and surface temperatures of crop tissue 44 . As a result, leaves, flowers and even the wider vegetated canopy can be cooler or warmer than the surrounding air 68,72 . In China and India, these crop influences on surface climate extend through the troposphere 73 and influence large-scale circulation and rainfall patterns 74 .…”
Section: Review Articlementioning
confidence: 99%
“…This approach strengthens crop-atmosphere interactions and worsens compound climate impacts on yields. However, soybean can maintain flower transpiration, whereas leaf stomates close during combined heat and drought, relatively cooling the heat-sensitive flowers by 2-3 °C 72 . Such physiological responses illustrate the diverse genetic potential for new breeding targets to maintain sufficient and stable yields under compound stresses 183 .…”
Section: Adaptation Avenues For Compound Extremesmentioning
confidence: 99%
“…While the differences in velocity between vegetative and reproductive organs could be associated with the type of transport, linear in leaves and cumulative in the carpels, the contrasting pattern may also respond to different regulatory mechanisms underlying flow velocity in source and sink organs. In source organs, the velocity is mainly controlled by stomatal conductance, whereas in sink organs, the underlying forces are less understood (Sinha et al ., 2022). Previous works evidenced that a variety of hydraulic traits governed hydration of flowers (Roddy et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…g ., the drought and heat wave episodes of 1980 and 1988 in the US that resulted in losses to agriculture estimated at $33 and 44 billion, respectively; Mittler, 2006; https://www.ncdc.noaa.gov/billions/), and their increased frequency requires special attention. Multiple studies have now shown that the molecular, physiological, and metabolic response of plants subjected to water deficit (WD), or heat stress (HS) is different from that induced in plants during a combination of WD and HS (WD+HS), and could involve conflicting pathways and/or responses (Mittler, 2006; Zandalinas et al, 2020b; Zandalinas et al, 2021; Sinha et al, 2022; Zandalinas and Mittler, 2022; Mittler et al, 2022). Moreover, it was found that when droughts and heat waves co-occur during the reproductive growth phase of crops, their impact is significantly higher than when they co-occur during vegetative growth (Mahrookashani et al, 2017; Lawas et al, 2018; Liu et al, 2020; Cohen et al, 2021b; Sinha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During WD stomata close to prevent water loss, but during HS stomata open to cool the leaf by transpiration (Nilson and Assmann, 2007; Lawson and Matthews, 2020; Xie et al, 2022). During a combination of WD and HS, stomata on leaves of many plants remain however closed and leaf temperature increases to levels that are even higher than that of HS alone; because the plant cannot cool its leaves by transpiration (Mittler, 2006; Sinha et al, 2022; Mittler and Zandalinas, 2022). We recently reported that during a combination of WD+HS, stomata on leaves of soybean plants are closed, while stomata on flowers of soybean (sepals) are open (Sinha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%